Sustainable food waste practice among small medium enterprise (SME) restaurant operators in peninsular Malaysia/ Nur Azimah Othman ... [et al.] - Othman, Nur Azimah; Simpong, Derweanna Bah; Abd Razak, Nurul Fardila; Saidi, Normaizatul Akma; Samengon, Harnidah; Ahmad, Ghazali (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
This study empirically investigates restaurant operators' role to implement sustainable food waste practices. Food waste is mostly associated with behaviours such as negligence or conscious decisions to throw out food. Restaurants have a credible share in municipal waste as one of the significant waste sources globally and in Malaysia. Therefore, this increases the necessity of studying waste management practices among restaurants. This study is structured through a self-administered survey with the east coast restaurant operators directly involved in SME related businesses. Data from 250 respondents were analysed using multivariate analysis using structural equation modeling (SEM) via PLS. An exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were executed to validate the scales. These findings can be used by restaurant operators, through its dimensions, influence the adaptation mediating effects and create sustainable food waste practices.